The Solute Carrier MFSD1 Decreases the Activation Status of β1 Integrin and Thus Tumor Metastasis - Roblek, Marko; Bicher, Julia; van Gogh, Merel; György, Attila; Seeböck, Rita; Szulc, Bozena; Damme, Markus; Olczak, Mariusz; Borsig, Lubor; Siekhaus, Daria E. (Frontiers in Oncology, 2022)
Solute carriers are increasingly recognized as participating in a plethora of pathologies, including cancer. We describe here the involvement of the orphan solute carrier MFSD1 in the regulation of tumor cell migration. Loss of MFSD1 enabled higher levels of metastasis in experimental and spontaneous metastasis mouse models. We identified an increased migratory potential in MFSD1-/- tumor cells which was mediated by increased focal adhesion turn-over, reduced stability of mature inactive β1 integrin, and the resulting increased integrin activation index. We show that MFSD1 promoted recycling to the cell surface of endocytosed inactive β1 integrin and thereby protected β1 integrin from proteolytic degradation; this led to dampening of the integrin activation index. Furthermore, down-regulation of MFSD1 expression was observed during early steps of tumorigenesis and higher MFSD1 expression levels correlate with a better cancer patient prognosis. In sum, we describe a requirement for endolysosomal MFSD1 in efficient β1 integrin recycling to suppress tumor cell dissemination.